Designing Fully Populated Phased Arrays for Noninvasive Ultrasound Surgery with Controlled Degree of Irregularity in the Arrangement of Elements - Rosnitskiy, P. B.; Sapozhnikov, O. A.; Gavrilov, L. R.; Khokhlova, V. A. (Acoustical physics, 2020)
When designing phased antenna arrays for use in noninvasive ultrasound surgery, it is desirable to provide the highest possible power for a given array dimensions. At the same time, it is necessary to take into account the limitations on the maximum allowable ultrasound intensity at the array elements and to ensure suppression of spurious diffraction maxima in the spatial structure of the emitted field. The problem can be solved by designing an irregular arrangement combined with the densest filling of the array surface with elements. This paper presents a modification of such a method for creating fully populated arrays with nonperiodic tessellation distribution of elements, based on the restriction of the relaxation mechanism in an iterative array design algorithm. A computer model that allows for controlling the degree of irregularity in distribution of the array elements was developed. The stability of maintaining the low level of acoustic intensity in unwanted grating lobes was tested for various random realizations of the element arrangements by analyzing a statistical ensemble of 500 model arrays. The advantages of the considered arrays in comparison with existing models of fully populated arrays are demonstrated.